The Anterior Intrapelvic Approach for Acetabular Fractures Using Approach-Specific Instruments and an Anatomical-Preshaped 3-Dimensional Suprapectineal Plate. Issue 7 (July 2017) - Gras, Florian; Marintschev, Ivan; Grossterlinden, Lars; Rossmann, Markus; Graul, Isabel; Hofmann, Gunther O.; Rueger, Johannes M.; Lehmann, Wolfgang
Abstract : Objectives: Anatomical acetabular plates the anterior intrapelvic approach (AIP) were recently introduced to fix acetabular fractures through the intrapelvic approach. Therefore, we asked the following: (1) Does the preshaped 3-dimensional suprapectineal plate interfere with or even impair the fracture reduction quality? (2) How often does the AIP approach need to be extended by the first (lateral) window of the ilioinguinal approach? Design: Observational case series. Setting: Two Level 1 trauma centers. Patients/Participants: Patients with unstable acetabular fractures in 2014. Intervention: Fracture fixation with anatomical-preshaped, 3-dimensional suprapectineal plates through the AIP approach ± the first window of the ilioinguinal approach. Outcome Measurements: Fracture reduction results were measured in computed tomography scans and graded according to the Matta quality of reduction. Intraoperative parameters and perioperative complications were recorded. Radiological results (according to Matta) and functional outcome (modified Merle d'Aubigné score) were evaluated at 1-year follow-up. Results: Thirty patients (9 women + 21 men; mean age ± SE: 64 ± 8 years) were included. The intrapelvic approach was solely used in 19 cases, and in 11 cases, an additional extension with the first window of the ilioinguinal approach (preferential for 2-column fractures) was performed. The mean operating time was 202 ± 59 minutes; the fluoroscopic time was 66 ± 48 seconds. Fracture gaps and steps in preoperative versus postoperative computed tomography scans were 12.4 ± 9.8 versus 2.0 ± 1.5 and 6.0 ± 5.5 versus 1.3 ± 1.7 mm, respectively. At 13.4 ± 2.9 months follow-up, the Matta grading was excellent in 50%, good in 25%, fair in 11%, and poor in 14% of cases. The modified Merle d'Aubigné score was excellent in 17%, good in 37%, fair in 33%, and poor in 13% of cases. Conclusion: The AIP approach using approach-specific instruments and an anatomical-preshaped, 3-dimensional suprapectineal plate became the standard procedure in our departments. Radiological and functional early results justify joint preserving surgery in most cases. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.